White Matter Governed Superior Frontal Sulcus Surgical Paradigm: A Radioanatomic Microsurgical Study—Part II. Issue 4 (11th May 2020) - Kassam, Amin B; Monroy-Sosa, Alejandro; Fukui, Melanie B; Kura, Bhavani; Jennings, Jonathan E; Celix, Juanita M; Nash, Kenneth C; Kassam, Mikaeel; Rovin, Richard A; Chakravarthi, Srikant S
Abstract: BACKGROUND: Kocher's point (KP) and its variations have provided standard access to the frontal horn (FH) for over a century. Anatomic understanding of white matter tracts (WMTs) has evolved, now positioning us to better inform the optimal FH trajectory. OBJECTIVE: To (1) undertake a literature review analyzing entry points (EPs) to the FH; (2) introduce a purpose-built WMT-founded superior frontal sulcus parafascicular (SFSP)-EP also referred to as the Kassam-Monroy entry point (KM-EP); and (3) compare KM-EP with KP and variants with respect to WMTs. METHODS: (1) Literature review (PubMed database, 1892-2018): (a) stratification based on the corridor: i. ventricular catheter; ii. through-channel endoscopic; or iii. portal; (b) substratification based on intent: i. preoperatively planned or ii. intraoperative (postdural opening) for urgent ventricular drainage. (2) Anatomic comparisons of KM-EP, KP, and variants via (a) cadaveric dissections and (b) magnetic resonance-diffusion tensor imaging computational 3D modeling. RESULTS: A total of 31 studies met inclusion criteria: (a) 9 utilized KP coordinate (1 cm anterior to the coronal suture (y-axis) and 3 cm lateral of the midline (x-axis) approximated by the midpupillary line) and 22 EPs represented variations. All 31 traversed critical subcortical WMTs, specifically the frontal aslant tract, superior longitudinal fasciculus II, and inferior fronto-occipital fasciculus, whereas KM-EP (x = 2.3, y = 3.5) spares these WMTs. CONCLUSION: KP (x = 3, y = 1) conceived over a century ago, prior to awareness of WMTs, as well as its variants, anatomically place critical WMTs at risk. The KM-EP (x = 2.3, y = 3.5) is purpose built and founded on WMTs, representing anatomically safe access to the FH. Correlative clinical safety, which will be directly proportional to the size of the corridor, is yet to be established in prospective studies.